2019
DOI: 10.1039/c9cy00846b
|View full text |Cite
|
Sign up to set email alerts
|

The role of the molecular formula of ZnCl2·nH2O on its catalyst activity: a systematic study of zinc chloride hydrates in the catalytic valorisation of cellulosic biomass

Abstract: We show the efficient and direct transformation of a range of low value cellulosic substrates such as lignocellulose and algal biomass, into higher value chemicals, including low molecular weight reducing saccharides and furanoid products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Conversions of softwood-derived cellulose in ZnCl 2 ·4.25H 2 O, co-solvent system comprising [C 4 mim]Cl and ChCl/oxalic acid, or in ethanol (water content < 0.2%) were performed according to the respective references.…”
Section: Methodsmentioning
confidence: 99%
“…Conversions of softwood-derived cellulose in ZnCl 2 ·4.25H 2 O, co-solvent system comprising [C 4 mim]Cl and ChCl/oxalic acid, or in ethanol (water content < 0.2%) were performed according to the respective references.…”
Section: Methodsmentioning
confidence: 99%
“…The cellulose chain gains flexibility, and therefore, water molecules penetrate the network, producing the dissolution of cellulose. 37 Several studies have investigated the dissolution and hydrolysis of cellulose dissolved in inorganic salt hydrates; 7,38,39 however, the separation of obtained sugars from inorganic salt hydrates is very difficult due to the high solubility of sugars in the dissolution media, and despite some promising studies, such separation remains a challenge. 38 The aim of this work is to study the dissolution of cellulose in different inorganic salt hydrates and its subsequent precipitation by the addition of excess water.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the coordinated water number influences the acidity and thus the catalytic activity [13b] . LiCl with 2–5 coordinated waters was separately examined for esterification of LA with BuOH.…”
Section: Resultsmentioning
confidence: 99%